IMPLEMENTATION OF ONLINE DISPUTE RESOLUTION (ODR) IN INDONESIA’S E-COMMERCE DISPUTES (COMPARATIVE STUDY WITH USA) - Haryanto, Imam; Sakti, Muthia (Jurnal Hukum dan Keadilan, 2024)
ODR is the best alternative dispute resolution option in resolving E-Commerce disputes. In 2020, BANI has implemented this mechanism, but there are still shortcomings in its application. Because the existing obstacles have not been fully resolved. Adopting, and imitating the mechanisms, processes, and arrangements of countries that have successfully implemented ODR in their countries is one way to make the implementation of this mechanism successful in Indonesia. The normative legal research method is used by the author in writing this final project. The theory used is legal protection and certainty. Legal protection is used so that in analyzing the formulation of the problem it remains to protect the community from the law that will apply without the interests of the authorities. Restorative justice is used when the author concludes the deficiencies in the comparison of the two countries. All of this is done so that the author can analyze and conclude about the opportunities and obstacles to the implementation of ODR in Indonesia, as well as draw conclusions regarding the comparison between the two countries, in this case the United States and Indonesia. So that in the future ODR can be used as an option by all LAPS and the government can issue special arrangements related to ODR so that people do not hesitate in choosing this option in alternative dispute resolution, both E-Commerce business disputes and other civil disputes.